2009 International Conference on Biometrics and Kansei Engineering 2009
DOI: 10.1109/icbake.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Model for E-learning Systems Using Kansei Engineering Techniques: A Preliminary Study

Abstract: The rapid development of information technology leads to extremely dynamic changes in various tools and technologies applied to the e-learning process. However, building computer devices or systems with the ability of responding to learner emotions is a challengeable task. Kansei Engineering, as a novel concept in the modern era of e-learning addresses the psychological feelings such as emotions, moods, and impressions of the e-learner. The aim of this research study is to introduce the background of Kansei En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…These knowledges will be translated into design elements, and then generate the formulation of a new product design that embeds consumers' implicit emotional feelings and desires. It is also an evident that kansei methodology can be used to enable attractive discussion in distance learning environment, as positive emotion has been found to positively associates with learning [14]- [18]. This research tries to adopt MADM into kansei engineering method especially in order to make a decision to select the suitable one from many alternative objects.…”
Section: Related Workmentioning
confidence: 99%
“…These knowledges will be translated into design elements, and then generate the formulation of a new product design that embeds consumers' implicit emotional feelings and desires. It is also an evident that kansei methodology can be used to enable attractive discussion in distance learning environment, as positive emotion has been found to positively associates with learning [14]- [18]. This research tries to adopt MADM into kansei engineering method especially in order to make a decision to select the suitable one from many alternative objects.…”
Section: Related Workmentioning
confidence: 99%
“…Emotions are important in adult e-learning because they can either obstruct or motivate learning. Moreover, recent research on the emotions of online learning has focused on the importance of learners' feelings in relation to the sense of community of learning [11]. Numerous academic research activities have been carried out to monitor the learning pattern of the learner in the face to face environment.…”
Section: B Learners' Emotional States Identified Mostlymentioning
confidence: 99%
“…Study in [17] reports the aspect of emotion in interactive e-Learning system with the use of biometric signal and Kansei engineering, by analyzing knowledge and emotion level. Study in [18] proposes a conceptual model for e-Learning using a software agent to recognize and respond to the learners' emotional state during learning phase. Other studies of Kansei engineering in e-Learning can be found in [19] which reports about Kansei semantic space in online database courseware systems and [20] which reports a theoretical framework of playful interaction in mobile learning system.…”
Section: Introductionmentioning
confidence: 99%